Death, Conflict and Scandal. A Practical Theological Study of the Role of Rituals in Congregations Following the Loss of the Minister - Marileen Steyn (Yearbook for Ritual and Liturgical Studies)
Summary of PhD Thesis. This thesis was defended on October 23, 2023 at Stellenbosch University (South-Africa). Supervisors: prof. dr. Cas Wepener (Stellenbosch University, South-Africa) and prof. dr. Christo Thesnaar (Stellenbosch University, South-Africa). The Pastoral Office of the Western Cape Synod of the Dutch Reformed Church in South Africa acted as the problem owner and the funder of the research.